2019
DOI: 10.33084/pedagogik.v14i1.831
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Model Pembelajaran Diagnostic terhadap Kemampuan Membaca Peserta Didik Kelas V SDN 4 Menteng Palangka Raya

Abstract: Penelitian ini bertujuan untuk mengetahui ada tidaknya pengaruh penggunaan model pembelajaran diagnostic terhadap kemampuan membaca pemahaman pada peserta didik kelas VSDN 4 Menteng Palangka Raya. Hasil penelitian menunjukkan adanya pengaruh penggunaan model Untuk membuktikanpembelajaran diagnostic terhadap kemampuan membaca pemahaman peserta didik kelas VSDN 4 Menteng Palangka Raya, hal ini dapat dilihat dari hasil perhitungan yang diperoleh thitung sebesar 17,87 selanjutnya di konsultasikan dengan tabel pada… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…Where 𝑠 can be obtained using the formula : These results also match those carried out by Hapsari, the ICARE learning model is effective and useful, learning outcomes increase by 18.5% (Hapsari et al, 2019). Furthermore Hadi concluded that by applying this model, his learning outcomes increased (Hadi, 2022).…”
Section: Uji Hipotesissupporting
confidence: 72%
“…Where 𝑠 can be obtained using the formula : These results also match those carried out by Hapsari, the ICARE learning model is effective and useful, learning outcomes increase by 18.5% (Hapsari et al, 2019). Furthermore Hadi concluded that by applying this model, his learning outcomes increased (Hadi, 2022).…”
Section: Uji Hipotesissupporting
confidence: 72%